2016
DOI: 10.3389/fmicb.2016.02110
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient CRISPR/Cas9-Mediated Homologous Recombination Promotes the Rapid Generation of Bacterial Artificial Chromosomes of Pseudorabies Virus

Abstract: Bacterial artificial chromosomes (BACs) are powerful tools for the manipulation of the large genomes of DNA viruses, such as herpesviruses. However, the methods currently used to construct the recombinant viruses, an important intermediate link in the generation of BACs, involve the laborious process of multiple plaque purifications. Moreover, some fastidious viruses may be lost or damaged during these processes, making it impossible to generate BACs from these large-genome DNA viruses. Here, we introduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Second, the linear or circular donor plasmids might also influence HR efficiency. In our study, we found that a linear donor plasmid is more effective than a circular donor plasmid (17). In another study, however, BAC clones of Epstein-Barr virus utilizing a circular donor plasmid were generated to enabled a higher efficiency (21).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Second, the linear or circular donor plasmids might also influence HR efficiency. In our study, we found that a linear donor plasmid is more effective than a circular donor plasmid (17). In another study, however, BAC clones of Epstein-Barr virus utilizing a circular donor plasmid were generated to enabled a higher efficiency (21).…”
Section: Discussionmentioning
confidence: 56%
“…Target sequences were synthesized and cloned into the PX330 vector (4), as previously reported (14). The sequences and incision efficiencies of pCas9-Us6, pCas9-Us8, pCas9-Us7, pCas9-Us9, and pCas9-Us2 have been previously described (17). The pCas9unique long (UL) region 24 (UL24) targeting site was 59-GCGGCACCGGCAAGAGCACCA-39, and the pCas9-UL24 targeting site was 59-GTGCGCCTTCACGTCGGAGAT-39.…”
Section: Sgrna Construction and Donor Plasmidmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, it has been widely used in genome editing of many viruses, such as herpes simplex virus (Lin et al, 2016;Roehm et al, 2016), adenovirus (Bi et al, 2014), hepatitis B virus (Liu et al, 2018), African swine fever virus (Borca et al, 2018;Hubner et al, 2018), and so on. However, most of manipulations were focuses on viral non-essential genes and on insertion of a foreign gene (Xu et al, 2015;Guo et al, 2016;Liang et al, 2016;Tang et al, 2016Tang et al, , 2017Tang et al, , 2018. There is no good approach to replace essential genes among the different PRV strains.…”
Section: Discussionmentioning
confidence: 99%